Why do galactic spins flip in the cosmic web? A Theory of Tidal Torques near saddles - Pichon, C; Codis, S; Pogosyan, D; Dubois, Y; Desjacques, V; Devriendt, J (Cambridge University Press, 2016)

(untitled)
Filaments of the cosmic web drive spin acquisition of disc galaxies. The point process of filament-type saddle represent best this environment and can be used to revisit the Tidal Torque Theory in the context of an anisotropic peak (saddle) background split. The constrained misalignment between the tidal tensor and the Hessian of the density field generated in the vicinity of filament saddle points simply explains the corresponding transverse and longitudinal point-reflection symmetric geometry of spin distribution. It predicts in particular an azimuthal orientation of the spins of more massive galaxies and spin alignment with the filament for less massive galaxies. Its scale dependence also allows us to relate the transition mass corresponding to the alignment of dark matter halos spin relative to the direction of their neighboring filament to this geometry, and to predict accordingly it s scaling with the mass of non linearity, as was measured in simulations.